IJCM_39A: To compare the World Health Organization growth charts with Indian Academy of Pediatrics growth charts of under-five children attending urban health center of a Medical College - Muntazeem Muhammed G; Kumar Aswin (Wolters Kluwer Medknow Publications, 2024)
Background: The nutritional status of the child can be measured by using anthropometry which is the valuable tool and the gold standard method. The magnitude of different measures of nutritional status is affected by choice of reference charts used. Objective: To compare the world Health Organization growth charts with Indian academy of pediatrics growth charts to assess the malnutrition among under 5 children attending Urban health center of a medical College. Methodology: A cross sectional study was conducted among 220 children attended urban health centre of SS. Institute of Medical Sciences for a period of 4 months. Height and weight were measured and plotted on World Health Organization and Indian Academy of Pediatrics charts. Results: In this study underweight was detected among 46.9% of the boys and 43.8% of the girls and stunting was detected among 50.4% of the boys and 43.8% of the girls by using World Health Organization Growth Charts. According to Indian academy of Pediatrics, 32.1% of the boys and 38% of the girls were found to be undernourished and Stunting was detected among 53.9% of the boys and 68.8% of the girls. Conclusion: In this study both the growth charts showed variation in the height and weight measurements.